Pendidikan Jasmani dalam Kitab At-Tahliyyah Wa At-Targhib dan Implikasinya dalam Pendidikan Islam - Hakiman, Hakiman; Mustofa, Kholid Khamdan (Universitas Islam Sultan Agung, 2022)
This study aims to find and describe the form of physical education in the book at-tahliyyah wa at-targhib by Sayyid Affandi Muhammad and its implications in Islamic education. This research is a library research with primary data from books and supported by secondary data to deepen this research. The data collection technique uses documentation, while the analysis uses content analysis. The results showed that physical education in the book at-tahliyyah wa at-targhib is following health rules in dressing, following health rules about housing, maintaining cleanliness, treating disease, getting used to exercise and regulating eating and drinking patterns. And the implication in Islamic education is that the goal of Islamic education is to form Insan al-kamil. These goals can be internalized in the curriculum. Meanwhile, educators can use the motion method as a learning method in PAI. Then for students is to pay attention and apply it such as maintaining cleanliness and maintaining their diet in everyday life.